ANCIENT LINEAR FORTIFICATION ON THE LOWER DANUBE. - Adrian-Viorel Martin (Journal of Ancient History and Archaeology)
Ancient Linear Fortification on the Lower Danube. Proceedings of the National Colloquium. (Brăila, 14-16 iunie, 2013),editors: Valeriu Sîrbu, Costin Croitoru. Mega Publishing House, 2014. pp.189. ISBN 978-606-543-529-2.